2011
DOI: 10.1159/000327949
|View full text |Cite
|
Sign up to set email alerts
|

Deltonin, a Steroidal Saponin, Inhibits Colon Cancer Cell Growth <i>in Vitro</i> and Tumor Growth <i>in Vivo</i> via Induction of Apoptosis and Antiangiogenesis

Abstract: Deltonin, a steroidal saponin, isolated from Dioscorea zingiberensis Wright (DZW), has shown high-cytotoxic activity in cancer cells. However, its mechanisms and in vivo anti-cancer effects remain unknown. In the present study, we evaluated the effects and explored the anti-tumor mechanisms of deltonin on a panel of colon cancer cell lines and in a mouse model of murine colon cancer C26. Deltonin had more cytotoxic effect on C26 cells than 5-fluorouracil had, promoting dramatic G2-M phase arrest and apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…For example, echinoside A, a saponin from the sea cucumber H. nobilis Selenka, induced apoptosis and inhibited tumor growth in a nude mouse xenograft tumor model by specifically antagonizing the binding of topoisomerase 2α to DNA, which is based on a highly enzyme-specific interaction. Similar effects were observed for deltonin, 62 alpha-tomatine, 23 and tubeimoside-1.…”
Section: Efficacy Of Saponins and Clinical Potentialsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, echinoside A, a saponin from the sea cucumber H. nobilis Selenka, induced apoptosis and inhibited tumor growth in a nude mouse xenograft tumor model by specifically antagonizing the binding of topoisomerase 2α to DNA, which is based on a highly enzyme-specific interaction. Similar effects were observed for deltonin, 62 alpha-tomatine, 23 and tubeimoside-1.…”
Section: Efficacy Of Saponins and Clinical Potentialsupporting
confidence: 80%
“…For instance, deltonin, a steroidal monodesmosidic saponin from Dioscorea zingiberensis Wright, hampered tumor growth in tumor-bearing BALB/c mice after oral administration. 62 Similarly, timosaponin A-III, a steroidal saponin from Anemarrhena sphodeloides Bunge, slowed tumor growth in a xenograft tumor model in BALB/c-nu mice, 63 and ginsenoside Rg3, from the American ginseng, Panax quinquefolius L, inhibited growth of human colon cancer cells in a xenograft tumor model. 23 Suppressed tumor growth was also observed for other saponins like 51,52 and several other saponins.…”
Section: Efficacy Of Saponins and Clinical Potentialmentioning
confidence: 99%
“…Deltonin was obtained as previously described and its purity determined by high performance liquid chromatography (>98%) (19 (12, 24, 36, 48 h). All experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Deltonin, diosge nin- (15)(16)(17)(18). We have previously demonstrated that deltonin has cytotoxic effects against colon cancer cell lines and oral administration of deltonin was found to significantly inhibit tumor growth and prolonged survival of tumor bearing mice (19,20). However, the effects of deltonin in breast cancer remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The observed biological activities of T. terrestris are mainly due to its abundant steroidal saponins [10,11,12,13]. Researchers have focused on steroidal saponins as potential candidates for the development of chemotherapeutic agents due to their anticancer effects [14,15,16]. However, the potential anticancer effects of terrestrosin D (TED; fig.…”
Section: Introductionmentioning
confidence: 99%